Micro-SPE in pipette tips as a tool for analysis of small-molecule drugs in serum. (June 2017) - Vlčková, Hana; Pilařová, Veronika; Novák, Ondřej; Solich, Petr; Nováková, Lucie
Aim: Micro-SPE in pipette tips (μ-SPE-PT) with particle sorbent has never been used in small-molecule drug analysis.Methodology & results: μ-SPE-PT was used for the extraction of statins from biological materials followed by UHPLC–MS/MS. The commercial and homemade μ-SPE-PT tips filled with particle sorbent were compared. While the homemade tips enabled direct serum sample loading into the sorbent, protein precipitation (PP) had to be implemented before μ-SPE-PT procedure using commercial tips. Three μ-SPE-PT methods were developed and validated: method A: μ-SPE-PT with homemade tips; method B: PP + μ-SPE-PT with homemade tips; and method C: PP + μ-SPE-PT with commercial tips. Method A enabled a simple high-throughput approach (48 samples in 90 min) compared with methods B and C that required three-times longer time. However, PP increased the recoveries of protein-bound analytes and extracts purity in methods B and C. The matrix effects without internal standards correction for method C were significantly higher than those for the methods A and B.Conclusion: Compared with commercial tips, homemade tips filled with particles were found to be more suitable for drug analysis. Commercial tips tested in this study were found challenging but the conditions under which they could be applicable were also defined.